Neuroprotective Effects of a Multi-Herbal Extract on Axonal and Synaptic Disruption in Vitro and Cognitive Impairment in Vivo - Lin, Ni-Hsuan; Goh, Angela; Lin, Shyh-Horng; Chuang, Kai-An; Chang, Chih-Hsuan; Li, Ming-Han; Lu, Chu-Hsun; Chen, Wen-Yin; Wei, Pei-Hsuan; Pan, I-Hong; Perng, Ming-Der; Wen, Shu-Fang (JAD reports, 2023)
Background: Alzheimer’s disease (AD) is a multifactorial disorder characterized by cognitive decline. Current available therapeutics for AD have limited clinical benefit. Therefore, preventive therapies for interrupting the development of AD are critically needed. Molecules targeting multifunction to interact with various pathlogical components have been considered to improve the therapeutic efficiency of AD. In particular, herbal medicines with multiplicity of actions produce cognitive benefits on AD. Bugu-M is a multi-herbal extract composed of Ganoderma lucidum (Antler form), Nelumbo nucifera Gaertn., Ziziphus jujuba Mill., and Dimocarpus longan, with the ability of its various components to confer resilience to cognitive deficits. Objective: To evaluate the potential of Bugu-M on amyloid-β (Aβ) toxicity and its in vitro mechanisms and on in vivo cognitive function. Methods: We illustrated the effect of Bugu-M on Aβ25–35-evoked toxicity as well as its possible mechanisms to diminish the pathogenesis of AD in rat cortical neurons. For cognitive function studies, 2-month-old female 3×Tg-AD mice were administered 400 mg/kg Bugu-M for 30 days. Behavioral tests were performed to assess the efficacy of Bugu-M on cognitive impairment. Results: In primary cortical neuronal cultures, Bugu-M mitigated Aβ-evoked toxicity by reducing cytoskeletal aberrations and axonal disruption, restoring presynaptic and postsynaptic protein expression, suppressing mitochondrial damage and apoptotic signaling, and reserving neurogenic and neurotrophic factors. Importantly, 30-day administration of Bugu-M effectively prevented development of cognitive impairment in 3-month-old female 3×Tg-AD mice. Conclusion: Bugu-M might be beneficial in delaying the progression of AD, and thus warrants consideration for its preventive potential for AD.